Managing the hope and worry of housing renewal—supporting well‐being in the emerging community. (24th October 2018) - Abbott, Penelope; Brooker, Ron; Reath, Jennifer
Abstract: Issue addressed: Housing renewal is a common urban housing and development strategy internationally. An intended result is increased social inclusion and well‐being of residents through public housing de‐concentration. In this study, we examined challenges encountered during the process of housing renewal from the perspectives of community‐based staff and volunteers. Methods: We conducted semi‐structured qualitative interviews with housing and community workers, service managers and community volunteers who were working with residents experiencing housing renewal in an outer metropolitan estate in New South Wales. We analysed the data thematically. Results: Seventeen participants were interviewed in a mix of individual and group interviews. Housing workers uncovered substantial resident health and social support needs during housing assessments. Promoting access to services and supporting the mental health and social connectedness of residents into the future were seen as key goals and challenges. However, lack of clarity on which services and community resources would exist in the new neighbourhood at the completion of the renewal project made this more difficult, particularly when supporting the social housing residents who were remaining in the changing community. Conclusions: Supporting the mental health and well‐being of residents experiencing housing renewal is an important role of community‐based workers, volunteers and service providers. This includes facilitating access to health care and other services and promoting social connectedness in the emerging community. Increased clarity on what community resources and services will be available subsequent to redevelopment will assist in these aims. So what?: Early knowledge of what community resources and services will be in place long term in communities undergoing housing renewal will allow staff and volunteers to better support the health and well‐being of residents.